2021
DOI: 10.3390/v14010041
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs, from Evolutionary Junk to Possible Prognostic Markers and Therapeutic Targets in COVID-19

Abstract: The COVID-19 pandemic has been a public health issue around the world in the last few years. Currently, there is no specific antiviral treatment to fight the disease. Thus, it is essential to highlight possible prognostic predictors that could identify patients with a high risk of developing complications. Within this framework, miRNA biomolecules play a vital role in the genetic regulation of various genes, principally, those related to the pathophysiology of the disease. Here, we review the interaction of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 200 publications
0
27
0
Order By: Relevance
“…Viral miRNAs encoded by the SARS-CoV-2 genome guard their replication machinery and escape the host's immunity by targeting various host genes, finally attenuating it. Identification of viral miRNA could be accomplished by two main approaches, i.e., in silico analysis and sequencing of small cloned RNA [39] . Recent studies have predicted 3377 human target genes denoting it to be a unique target for 170 SARS-CoV-2 encoded matured miRNAs [40] .…”
Section: Mirnas As Therapeutic Biomarkermentioning
confidence: 99%
See 3 more Smart Citations
“…Viral miRNAs encoded by the SARS-CoV-2 genome guard their replication machinery and escape the host's immunity by targeting various host genes, finally attenuating it. Identification of viral miRNA could be accomplished by two main approaches, i.e., in silico analysis and sequencing of small cloned RNA [39] . Recent studies have predicted 3377 human target genes denoting it to be a unique target for 170 SARS-CoV-2 encoded matured miRNAs [40] .…”
Section: Mirnas As Therapeutic Biomarkermentioning
confidence: 99%
“…In-silico study of SARS-CoV-2 encoding miRNA targets the Ca2+ signaling pathway, which acts as a key activator that subsequently affects other signaling pathways branching it. A variety of prediction tools are used to compare the resemblance of small noncoding miRNA of the host to viral miRNAs to identify an efficient target to effectively build a human-friendly therapeutic vaccine [39] . One of the computational works of Tie Ying Yu et al has identified three miRNA precursor sequences with the help of BLAST analysis of novel SARS-CoV-2 and then functionally annotated mature and precursor sequences [53] .…”
Section: Mirnas As Therapeutic Biomarkermentioning
confidence: 99%
See 2 more Smart Citations
“…An important aspect of virus–host relation during SARS-CoV-2 infection and COVID-19 course is the role of miRNAs. This issue has been a subject of recent reviews [ 132 , 133 ]. One of the first known major modes of action of the virus on the host cell is sequestering of the host miRNAs [ 134 ].…”
Section: Final Remarksmentioning
confidence: 99%